MANAJEMEN PENGEMBANGAN PROFESIONALISME GURU DI SMP ISLAM TERPADU AR RAIHAN BANDAR LAMPUNG - Ashepi Zulham; Alben Ambarita; Sowiyah Sowiyah (9 772338317006)
The research was aims to analyze and describe the teacher professionalism development management comprised of; planning, controlling, actuating and controlling. The focus of this research are planning, organizing, actuating, and controlling of teacher professionalism development. Qualitativemethod with a case study design has been used in the research, adopting data collecting technique through observation, documentation and interviews. Source of the data used are The Head of Foundation, Principal, vice Principals and teachers. Triangulation was used to analyze the data. The result of the resource are: 1) Planningwas conducted as the reference in determining the programs in the future. 2) Organizingwasgood enough just Its not so optimal because Its need optimize in subject teacher discussion internal or external 3) Actuatingalready run well only still needs to be improved because the training that implemented is still per clump lesson. assessment system and applying teaching using media is given more of the meeting. 4) Controlling is conducted as the programs evaluation were. Penelitian ini adalah untuk menganalisis manajemen pengembangan profesionalisme guru di SMP Islam terpadu Ar Raihan Bandar Lampung.Fokus penelitian ini adalah perencanaan, pengorganisasian, pelaksanaan, dan pengawasan pengembangan profesionalisme guru. Penelitian ini menggunakan Metode kualitatif dengan rancangan studi kasus, teknik pengumpulan data melalui observasi, dokumentasi dan wawancara. Sumber data adalah Ketua Yayasan, kepala sekolah, wakil kepala sekolah, guru, orang tua dan komite. Analisis data yang digunakan dengan tringulasi, Hasil penelitian adalah: 1)perencanaan melihat dari analisis program yang telah dilakukan sebagai acuan dalam menentukan perencanaan program dimasa yang akan datang 2)pengorganisasian masih perlu dimaksimalkannya MGMP baik internal maupun eksternal 3) pelaksanaan berjalan dengan baik, perlu peningkatan dalam hal pelatihan yang selama ini pelaksanaanya baru bersifat perumpun pelajaran 4) pengawasan profesionalisme guru dilakukan sebagai evaluasi program yang telah dilakukan.Kata kunci: manajemen pengembangan, profesionalisme guru